Evaluasi Lahan Parkir Untuk Menentukan Daya Tampung Parkir Kendaraan Pada Area Pasar Blimbing Paciran - Zamroni, Sahrul; Agustapraja, Hammam Rofiqi; Arief, Samsul (Universitas Batanghari Jambi, 2025)
The Blimbing Paciran Market is a bustling economic activity center, but the available parking facilities are still limited and poorly organized. This causes parking irregularities and congestion around the market area. The main problem raised in this study is the suboptimal capacity of the parking area to accommodate the increasing number of vehicles, especially bemo vehicles. This study aims to evaluate the parking area at Blimbing Market, Paciran, in order to determine the optimal capacity for two-wheeled, three-wheeled, and four-wheeled vehicles. The research location experiences high market activity, yet the limited parking facilities often lead to disorganized parking and congestion. The research methods employed in this study are quantitative and qualitative approaches based on statistical analysis. The results of the study showed that over a 7-day observation period, the average accumulation per day was 37 motorcycles, 16 bemos (three-wheeled vehicles), and 6 cars. The average parking duration was 26 minutes for motorcycles, 29 minutes for bemos, and 29 minutes for cars. The average parking volume was recorded at 183 motorcycles, 40 bemos, and 23 cars. The parking index indicated average values of 38.99% for motorcycles, 129.76% for bemos, and 58.44% for cars. The average parking turnover rate was found to be 1.90 for motorcycles, 3.31 for bemos, and 2.08 for cars.